Impact of Climate Change on Human Security Among Vulnerable Indigenous Groups of Zangon Kataf Lga Area of Kaduna State, Nigeria - Ibrahim MUSA; Abiola Titus OLUSOLA; Sule MAGAJI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:This study examines the effects of climate change on human security among vulnerable groups in Zango Kataf Local Government Area, Kaduna State, Nigeria. It assesses trends in temperature, rainfall, and surface soil wetness (1989–2022) and their impacts on economic, food, health, environmental, personal, community, and political security.Methodology:The study adopted the cross-sectional survey research design. The design is suitable for collecting data through sampling when the population is too large to be investigated, as in the case of vulnerable groups in the Zango Kataf Local Government Area of Kaduna State. A cross-sectional survey design was used, combining climate data analysis with questionnaires administered to 400 residents in Zonkwa, Gora, Kamantan, and Madakiya.Findings:Findings revealed a 12% increase in average surface temperature from 1989 to 2022, with December being the coolest (21.83°C) and March the warmest (29.13°C). Rainfall decreased over the study period, with December (4.68mm) and February (6.15mm) recording the lowest levels. Surface soil wetness peaked in September (0.85m³) and was lowest in March (0.242m³). Statistical analysis demonstrated significant impacts of climate change on economic security (χ²(20) =100.076, p<.001, Cramer's V=0.500) and food security (χ²(8) =34.148, p<.001, Phi=0.292). Other security dimensions, including health and environmental security, showed strong associations with climate change, with Cramer's V values ranging from 0.292 to 0.705 (p<.001).Implication:The study recommends establishing climate monitoring stations to collect real-time data on temperature, rainfall, and soil wetness. These data will aid in developing adaptive strategies and early warning systems, mitigating climate-related risks and enhancing the resilience of vulnerable populations.